Cursive handwriting skills of primary school pre service teachers - Fetty Fellasufah; Ali Mustadi (Intelektual Pustaka Media Utama, 2019)
Normally, a pre service teacher will get an education in order to prepare themselves in cognitive knowledge, positive attitudes and skills. Moreover, what will be faced by them is educating children who are actually going through the initial stages of learning, namely reading, writing, and counting. Writing, especially cursive handwriting, helps children train their motor skills. To teach cursive handwriting, the pre service teacher should have good cursive handwriting skills. It would be nice if during their study, pre service teachers get cursive handwriting training. This article will describe the learning activities of primary teacher education program related to cursive handwriting. Qualitative studies were conducted on 39 students in the same class. The result shows that learning activities which implement planning, implementation and evaluation stages can support students' skills in cursive handwriting. This process is being implemented in order to prepare pre service teachers to have good cursive handwriting skill.